Colonial geopolitics and local cultures in the Hellenistic and Roman East (3rd century BC - 3rd century AD) (Oxford)
v, 218 sayfa
Keywords: “Colonial Geopolitics and Local Cultures in the Hellenistic and Roman East (3rd century BC - 3rd century AD) presents contributions taken in the main from a panel held during the Celtic Conference in Classics 2014 (Edinburgh, Scotland, June 25-28th 2014), but also incorporates a number of papers given previously at another panel which convened at Mamaia (Romania, September 23-27th, 2012). What changes in the material culture can we observe, when a state is overwhelming a local population with soldiers, katoikoi, and civil officials or merchants? One of the main concerns of local geopolitics was the central question of how agricultural land was distributed to the Greek or Roman colonists after it had been seized from the native population? In what way did the state watch over and administer the colonised territories? What were the exact social, legal, cultural and political relationships between the natives and the newcomers? Did the language of the colonists dominate the local vernacular language or not, and in what way? Did onomastics change or not in particular regions over centuries? What were the mutual influences between native and colonial cultures? This collection addresses these questions, focusing on the Hellenistic and Roman East“ --